2014
DOI: 10.1126/scitranslmed.3008182
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Persistent Fibrosis in Aging by Targeting Nox4-Nrf2 Redox Imbalance

Abstract: The incidence and prevalence of pathological fibrosis increase with advancing age, although mechanisms for this association are unclear. We assessed the capacity for repair of lung injury in young (2 months) and aged (18 months) mice. While the severity of fibrosis was not significantly different between these groups, aged mice demonstrated an impaired capacity for fibrosis resolution. Persistent fibrosis in lungs of aged mice is characterized by the accumulation of senescent and apoptosis-resistant myofibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
659
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 596 publications
(704 citation statements)
references
References 45 publications
39
659
2
4
Order By: Relevance
“…A transient senescence response was observed in fibroblasts from young mice with resolving bleomycin-induced fibrosis supporting a role for senescence in spontaneous lung fibrosis resolution. 51 However, there are accumulating data supporting the fact that prolonged activation of senescent pathways contributes to persistent pulmonary fibrosis. Pulmonary fibrosis is classically, but not exclusively, a disease of aging.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
See 2 more Smart Citations
“…A transient senescence response was observed in fibroblasts from young mice with resolving bleomycin-induced fibrosis supporting a role for senescence in spontaneous lung fibrosis resolution. 51 However, there are accumulating data supporting the fact that prolonged activation of senescent pathways contributes to persistent pulmonary fibrosis. Pulmonary fibrosis is classically, but not exclusively, a disease of aging.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
“…91 Although the aged lung is more susceptible to the onset of fibrosis, few studies in the lung or other organs specifically address the capacity for resolution of established fibrosis in aged models. Hecker et al 51 demonstrated that bleomycin-induced fibrosis resolution was impaired in aged mice. In contrast to younger mice where the senescence response was transient, persistent fibrosis in the aged mice was associated with a prolonged senescent and apoptosis-resistant phenotype of myofibroblasts.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of lungs to various endogenous and exogenous oxidants may elicit inflammatory and fibrotic responses, leading to impaired antioxidant capacity. 2 This may perpetuate the injury response and impede tissue regeneration with sustained fibrosis. This oxidant-antioxidant imbalance may be accentuated in aging.…”
Section: Fibrosis As a Disease Of Agingmentioning
confidence: 99%
“…112 More recent studies demonstrate that the up-regulation of NOX4 is coupled to Nrf2 induction, and this adaptive response is critical to apoptosis susceptibility of myofibroblasts and resolution of fibrosis in young mice. 2 In contrast, in aged mice, there is impaired Nrf2 activation leading to an altered NOX4-Nrf2 redox balance and acquisition of an apoptosis-resistant myofibroblast phenotype resulting in persistent fibrosis. 2 This supports a mechanism for the antagonistic pleotropic action of NOX4 that is determined by the activation.…”
Section: Nrf2 In Aging and Lung Fibrosismentioning
confidence: 99%